2018
DOI: 10.1128/aac.01741-17
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Toll-Like Receptor 9-CpG Oligodeoxynucleotides and Hepatitis B Virus Virions Leads to Entry Inhibition in Hepatocytes and Reduction of Alpha Interferon Production by Plasmacytoid Dendritic Cells

Abstract: We previously reported that Toll-like receptor 9 (TLR9)-CpG oligonucleotides could inhibit the establishment of hepatitis B virus (HBV) infections in hepatocytes. Our aim was to uncover the underlying mechanisms of this inhibition. HepaRG cells, RPMI-B lymphoblastoma cells, and primary plasmacytoid dendritic cells (pDCs) exposed to HBV and TLR9 ligands/agonists in various configurations were used. We observed an inhibition of HBV infection upon TLR9 stimulations only when agonist was applied during inoculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 45 publications
(65 reference statements)
1
11
0
1
Order By: Relevance
“…This control seems to be immune‐mediated as a result of reduction in HBsAg. It has been shown that large amounts of HBsAg have immunosuppressive effects in HBV infection and its clearance in the circulation establishes a more permissive immunological environment where functional control can be restored. Recent results indicate that REP 2139 exposure has no direct immunostimulatory properties .…”
Section: Discussionmentioning
confidence: 99%
“…This control seems to be immune‐mediated as a result of reduction in HBsAg. It has been shown that large amounts of HBsAg have immunosuppressive effects in HBV infection and its clearance in the circulation establishes a more permissive immunological environment where functional control can be restored. Recent results indicate that REP 2139 exposure has no direct immunostimulatory properties .…”
Section: Discussionmentioning
confidence: 99%
“…Among agonists of pattern recognizing receptors expressed in primary liver cells 25 , namely agonists of Toll-like receptors (TLRs) attracted interest because of their potency to induce IFNs and proinflammatory cytokines and chemokines in both hepatocytes and non-parenchymal cells 23 , 24 . Moreover, it was shown that GS-9620 (vesatolimod), an agonist of endosomal TLR7, which is preferentially expressed in plasmacytoid dendritic cells (pDCs) 26 30 but not in primary hepatocytes (PHH) 23 , 31 , 32 , significantly reduced viremia and cccDNA expression, and led to functional cure in animal models 20 22 . A recent study showed that TLR1/2 and TLR3 ligands inhibit HBV replication in PHH, and that the same ligands also induce the production of antiviral cytokines in peripheral blood mononuclear cells (PBMCs) 23 .…”
Section: Introductionmentioning
confidence: 99%
“…CpG寡脱氧核苷酸是TLR9激动剂, 其处理浆细胞样树 突状细胞(plasmacytoid dendritic cell, pDC)和B细胞后 可以诱导IFN-α的产生 [142] . 用CpG 21798与恩替卡韦…”
Section: Hbv特异性cd8unclassified